RELEVANSI PAI DALAM KEHIDUPAN MODERN DI SMA PLUS PARIWISATA BANDUNG - Agus Hermawan; Aceng Nurul Huda; Helmawati; Iyad Suryadi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the application of the relevance of Islamic Religious Education (PAI) in the modern lives of students at Bandung Tourism High School. In the era of globalization and technological advancement, the younger generation faces significant challenges in maintaining religious values ​​amidst the currents of modernization, especially in a tourism education environment that is open to cultural and lifestyle diversity. This study uses a descriptive qualitative approach. This approach was chosen because it is appropriate for exploring and understanding the meaning, experiences, and interpretations of informants regarding the application of Islamic Religious Education (PAI) in the context of modern life in a tourism-based high school environment. Data collection techniques were carried out through observation, in-depth interviews, and documentation of PAI teachers, students, and school officials. The results of the study indicate that PAI teachers have a contextual understanding of the challenges of modern life. Teachers not only teach PAI normatively, but also align the material with contemporary issues relevant to the students' world, such as technology, adolescent lifestyles, and ethics in the tourism workplace. This builds students' understanding that Islamic teachings remain relevant and necessary in facing the challenges of the modern era. Students respond positively to the application of Islamic values ​​in the context of modern life. Most students found it helpful to understand religious values ​​through a contextual approach. They stated that Islamic Religious Education is not just a theory, but a guide to life